The most common technical errors in ice hockey shooting - Kornilov, R. (Haaga-Helia University of Applied Science, 2019)
The objective of this study is to gather theoretical and practical knowledge about ice hockey shooting techniques and examine what is required to learn the skill of shooting. It discusses a two-year-long project, the aim of which was to determine the most common technical errors in youth hockey. This thesis describes the basic shooting techniques from both a technical and a theoretical point of view and examines the steps involved in learning these techniques. This should be useful for those interested in shooting techniques and coaching.